Pelatihan Cinta Lingkungan: Pemanfaatan Sampah Plastik dan Penghijauan di SDIT Darul Aman - Alifia, Novita Putri; Anestya, Deladika Putri; Gustira, Nicolas Galang; Kurniawan, Fendi; Chasanah, Silvia Nidhaul; Nugraha, Joko Tri (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Plastic waste is a major problem in Indonesia, particularly in educational settings, where waste management is suboptimal. The goal of this community service activity is to create a green school environment by increasing students' awareness, skills, and responsibility for plastic waste management. Darul Aman Islamic Elementary School (SDIT) in Pringsurat District, Temanggung Regency with 48 students in grades 5 and 6, is the community service partner. The methods used were outreach, training, and hands-on practice with a participatory and educational approach through three stages: preparation, implementation, and evaluation. The results of the activity showed that students had a better understanding of how to recycle plastic waste and the importance of greening. As part of the school greening movement, students transformed used plastic gallons into beautiful and useful plant pots. This activity not only reduced the amount of plastic waste but also expanded green space in the school and fostered environmental awareness. This program has the potential to become a model for environmental learning that can be implemented in other schools.